Respuesta :
In short there are 35 yellow marbles and 14 blue marbles. For a long explanation, lol, keep on reading.
We know there are 49 marbles but we also know that there are only two colors, yellow and blue. So, we can assume that the yellow + blue marbles = 49. I'm going to use Y for yellow and B for blue. I'm going to rewrite the same equation with these variables. Y + B = 49. The problem continues with telling us that the yellow marbles are three times more than the blue ones with seven subtracted from that. I rephrased what they told us for better comprehension. So, we can assume that Y = 3B - 7. I gave Y that equation because of what the problem told us about Y. Continuing on, we know that Y + B = 49 and Y = 3B - 7. With this information, we can substitute Y into the Y + B = 49 equation. We now get, once we substitute Y into that equation, (3B - 7) + B = 49. We can add the B's together and get 4B - 7 = 49. Now, add the 7 and we get 4B = 56. Divide the B by 4 and we get B = 14. So, we now know what B is; we plug into the original equation to find Y. We plug in B = 14 into this equation, Y + B = 49. Once B is plugged in, Y + 14 = 49. Subtract 14 from 49 and we get Y = 35. Hope this helped. Good luck!
We know there are 49 marbles but we also know that there are only two colors, yellow and blue. So, we can assume that the yellow + blue marbles = 49. I'm going to use Y for yellow and B for blue. I'm going to rewrite the same equation with these variables. Y + B = 49. The problem continues with telling us that the yellow marbles are three times more than the blue ones with seven subtracted from that. I rephrased what they told us for better comprehension. So, we can assume that Y = 3B - 7. I gave Y that equation because of what the problem told us about Y. Continuing on, we know that Y + B = 49 and Y = 3B - 7. With this information, we can substitute Y into the Y + B = 49 equation. We now get, once we substitute Y into that equation, (3B - 7) + B = 49. We can add the B's together and get 4B - 7 = 49. Now, add the 7 and we get 4B = 56. Divide the B by 4 and we get B = 14. So, we now know what B is; we plug into the original equation to find Y. We plug in B = 14 into this equation, Y + B = 49. Once B is plugged in, Y + 14 = 49. Subtract 14 from 49 and we get Y = 35. Hope this helped. Good luck!